Defining Contemporaneity: Imagining Planetarity - Smith, Terry (The Nordic Journal of Aesthetics, 2016)
If the contemporaneity of difference seems the most striking characteristic of contemporary life today, its conceptual structure continues to elude definition. The same lack of clarity attends a frequently evoked parameter for the most desired resolution of such volatile differences: a cohesive, consensual world picturing, sometimes named “planetarity.” My overall project is a close examination of these two concepts, aimed at finding productive connections between them. Previous attempts to think them, from the confessions of St Augustine to the New York Times columns of Thomas Friedman, reveal a plethora of illuminating insights, but the overall record reveals that both concepts remain inadequately imagined for current circumstances. Temporality and world-being seems to constellate around these concepts: contemporaneity, history, decoloniality, connectivity, artworlds, and planetarity. How might the contemporaneity of difference and the embattled yet emergent planetary commons be imagined in terms appropriate to present need – that is, as contemporaneous, differential and convergent? While this question is obviously of the broadest relevance, my specific goal within the history and theory of art and architecture is to articulate the conceptual structure underlying my recent accounts of the relationships between contemporary art and architecture and contemporary life.